Water sustainability: between water quality and water quality modeling - Ujang, Zaini; Zainudin, Zaki (Institution of Engineers Malaysia, 2010)
Water quality modelling is an important tool used in various water quality management proceedings throughout the world. There are many types of models available, both commercially and as freeware for application in various hydrologic environments. The accuracy of a model in representing the myriad of physico- chemical and biological processes is entirely dependent on underlying mathematical formulations which form the basis of the model as well as the competency of the model developer or modeller. Data requirements, morphology, kinetics, model limitations, calibration and model validation all have to be considered and scrutinized before a water quality model can be accepted to be representative of the intrinsic conditions within a water body. Such detail and complexity is not only necessary to ensure accuracy, but also to assess the mitigation and pollution control measures in a sustainable fashion. In recent years, the adoption of water quality models in Malaysia has been extensive, for both river rehabilitation and impact assessment. They have been used to determine the Waste Assimilative Capacity (WAC) of a given water column; and to derive the maximum amount to pollution loading (Total Maximum Daily Load (TMDL)), from both point and non-point sources, that can enter the water column without seriously deteriorating ambient conditions; hence compromising its beneficial use. The assessment needs to be done under a wide array of hydraulic conditions, to ensure that temporal (seasonal) variations are also captured. In addition, there may also be other significant factors not completely encompassed in a particular model but are apparent to the water body of interest, which requires equivalent attention for a more representative outcome. Under these circumstances, an appropriate level of judgement needs to be practised through field survey proceedings so that the variation can at least, to a certain extent, be accounted for and margin of error minimized.